2017
DOI: 10.1021/acschembio.7b00469
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Association Dictates Ligand Specificity for the Innate Immune Receptor NOD2

Abstract: The human gut must regulate its immune response to resident and pathogenic bacteria, numbering in the trillions. The peptidoglycan component of the bacterial cell wall is a dense and rigid structure that consists of polymeric carbohydrates and highly cross-linked peptides which offers protection from the host and surrounding environment. Nucleotide-binding oligomerization domain-containing protein 2 (NOD2), a human membrane-associated innate immune receptor found in the gut epithelium and mutated in an estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 43 publications
(114 reference statements)
0
37
0
Order By: Relevance
“… 27 Recently, we have developed robust solution chemistry to access amino versions of peptidoglycan fragments which utilizes a benzyl protected carbohydrate ( 5 , Scheme 1 ). 26 Here, a tripeptide ( 7 , Scheme 1 ), which contains benzyl protecting groups, was synthesized using solution based chemistry (see the Supporting Information for synthetic details; Supplemental Scheme 1 ). 7 was coupled to 5 using coupling reagents to minimize epimerization, and the resulting product was globally deprotected using catalytic hydrogenation to yield 4 , a novel MTP whose tripeptide contains l -alanine, d -isoglutamine, and l -lysine.…”
Section: Resultsmentioning
confidence: 99%
“… 27 Recently, we have developed robust solution chemistry to access amino versions of peptidoglycan fragments which utilizes a benzyl protected carbohydrate ( 5 , Scheme 1 ). 26 Here, a tripeptide ( 7 , Scheme 1 ), which contains benzyl protecting groups, was synthesized using solution based chemistry (see the Supporting Information for synthetic details; Supplemental Scheme 1 ). 7 was coupled to 5 using coupling reagents to minimize epimerization, and the resulting product was globally deprotected using catalytic hydrogenation to yield 4 , a novel MTP whose tripeptide contains l -alanine, d -isoglutamine, and l -lysine.…”
Section: Resultsmentioning
confidence: 99%
“…NF‐κB luciferase assay : An established assay was used . See the Supporting Information for additional details/statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…NF- K B is also activated through a signal cascade in phagocytes via the recognition by the intracellular receptors nucleotide-binding oligomerization domain-containing protein 1 and 2 (NOD1 and NOD2). Gram-negative, and some Gram-positive, PG fragments containing γ- d -Glu- m DAP activate NOD1, while it has been demonstrated that for NOD2, the minimal fragment needed for recognition is a MurNAc residue, suggesting that it could function as a universal PG receptor [30,31]. It should be noted, however, that although lysozyme-released fragments adequately stimulate TLR2 and NOD2, released monomers containing 1,6-anhMurNAc products have been shown to have much weaker activation abilities [32].…”
Section: Peptidoglycan and Host Immune Interactionsmentioning
confidence: 99%